Inter‐Model Comparison of Delft3D‐FM and 2D HEC‐RAS for Total Water Level Prediction in Coastal to Inland Transition Zones. (26th July 2021) - Muñoz, David F.; Yin, Dongxiao; Bakhtyar, Roham; Moftakhari, Hamed; Xue, Zuo; Mandli, Kyle; Ferreira, Celso
Abstract: Hydrodynamic models play a key role in simulating total water level (TWL), that is, a combination of river flow, tide, surge, wind and wave‐induced water level, and representing flood inundation dynamics in coastal areas. An appropriate selection of two‐dimensional (2D) models that integrate riverine and estuarine interactions with ocean dynamics is crucial to generate accurate TWL predictions and assist stakeholders and federal agencies in decision making and flood emergency responses. In this study, we compare the performance of two widely used hydrodynamic models (e.g., 2D HEC‐RAS and Delft3D‐Flexible Mesh [FM]) with respect to their ability of predicting TWL in Delaware Bay, United States. Based on a previously established model configuration, we simulate Hurricane Sandy and Isabel that affected the Bay and led to considerable damages and economic losses. We then evaluate model capabilities with tidal analysis, compare observed vs. simulated TWL and analyze spatiotemporal variations of TWL through scenario‐based simulations. Our results suggest that atmospheric forcing input in Delft3D‐FM significantly improves TWL predictions as compared to those of 2D HEC‐RAS. Furthermore, model simulations with Delft3D‐FM can be faster than 2D HEC‐RAS by a factor of 6–10. Despite these advantages, 2D HEC‐RAS (version 5.07) is a noncommercial software easier to implement and can be a simpler alternative for modeling extreme events when atmospheric forcing is not relevant in the model domain.